Psychometric properties of a scale of innovative behavior in Ecuador (2018)
The purpose of the article is to validate in Ecuador employees, a scale of innovative behavior. The study was conducted in two universities in Guayaquil, Ecuador with a sample of 610 postgraduate students working in various companies in the economic sector. Through the exploratory and confirmatory factorial analysis, the reliability and validity of the scale was demonstrated. The results showed a one-dimensional scale with good psychometric properties. It is concluded that the instrument represents an interesting contribution to evaluate and identify the specific characteristics of the innovative behavior of the employees and constitutes a useful tool to improve the innovation processes of the companies in the Ecuadorian context. © 2018.